Efficacy and Safety of Stem Cell Therapy for Spinal Cord Injury in Adults: A Systematic Review and Meta-Analysis - Anadya Rhadika; Sultan Adhitya Romano; Himawan Widyatmiko; Andrew Wilbert Tanuwijaya; Putu Surya Pradipta Hariantha Putra; Salma Rizqi Amanah; Abdelrahman Ramadan Elashry; Sarmad Javaid; Made Agus Mahendra Inggas; Jeremiah Hilkiah Wijaya (Medicinus, 2025)
Background: Despite encouraging early results, clinical outcomes remain inconsistent across trials. This study aimed to systematically evaluate the efficacy and safety of stem cell therapy in adults with spinal cord injury (SCI). Methods: A systematic review and meta-analysis were conducted following PRISMA 2020 guidelines. PubMed, EMBASE, and Scopus were searched until 18 October 2025. Eligible studies included adult SCI patients receiving stem cell therapy with measurable neurological outcomes. Data synthesis was performed using Review Manager 5.4 under a random-effects model, reporting pooled risk ratios (RR) with 95% confidence intervals (CIs). Risk of bias was assessed using ROBINS-I, and evidence certainty was graded via GRADE. Result: Thirteen studies involving 470 participants (286 intervention, 184 control) were included. Stem cell therapy significantly improved neurological recovery compared with controls (RR = 2.64; 95% CI 1.70–4.10; p < 0.0001; I² = 0%). Subgroup analyses showed consistent benefits across baseline AIS classifications (RR = 2.61; 95% CI 1.71–3.98) and cell doses (RR = 2.75; 95% CI 1.63–4.64). No major safety signals were identified. GRADE assessment rated the certainty of efficacy evidence as moderate. Conclusions: Stem cell therapy yields significant neurological improvement in adult SCI with a favorable safety profile. The findings support its regenerative potential through neuroprotective and remyelinating mechanisms. However, larger randomized controlled trials are required to validate efficacy, optimize protocols, and assess long-term safety.